Futures Brokerage Companies Roles in Introducing the Futures Brokerage Industry to the Public Through Webinars: Peran Perusahaan Pialang Berjangka Dalam Mengenalkan Industri Pialang Berjangka Kepada Masyarakat Melalui Webinar - Intan Rizka Auliya; Sulastri Irbayuni (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Webinars are a powerful tool for combating misinformation about the futures brokerage industry. In collaboration with PT VIF Ciputra World, this community service activity took the form of a webinar. The primary goal was to educate participants from diverse social backgrounds. Results showed that 96% of participants were satisfied and gained a better understanding of the intricacies, legalities, and risks and opportunities of trading. This activity demonstrates that digital education is an effective way to introduce the futures brokerage industry in a positive and broad way. Going forward, collaboration and a variety of other media are needed to educate more people.